Wireless Security Threats - Umair Jilani; Muhammad Umar Khan; Adnan Afroz; Khawaja Masood Ahmed (Sir Syed University Research Journal of Engineering and Technology, 2013)
Wireless Communication Technologies has completely revolutionized the world. Wireless Communication Technologies provide ease to the users such as portability of the devices and mobile access to the internet. These portable wireless devices include PDAs, laptops, smart phones etc. offers some valuable features. These features include accessing the e-mails, SMS, MMS, calendars, addresses, phone numbers list and the internet. These entire devices store large amount of data and their wireless connection to network spectrum exhibit them as important source of computing. These devices are always vulnerable to attacks. Mobile devices are the new frontier for viruses, spam and other potential security threats. All these viruses, spam, Trojans and worms are out there in our vicinity to gain access to our personal data. This research aims to analyze the threats of viruses in the wireless communication systems and security including their role in the service outbreak, laying down the possible scenarios and also identifying possible remedies.